Animal Welfare and Livestock Supply Chain Sustainability Under the COVID-19 Outbreak: An Overview - Hashem, Nesrein M.; González-Bulnes, Antonio; Rodriguez-Morales, Alfonso J. (Frontiers in Veterinary Science, 2020)
The COVID-19 pandemic caused by the emergence, around the end of December 2019, of a new strain of coronaviruses (SARS-CoV-2) has caused both a public health and a socio-economic crisis worldwide during the 2020. The lockdown imposed to cope with the outbreak of the disease have dramatically challenged and negatively affected all the economic sectors of the modern global economy. Among them, livestock sector and related industries are among the most impacted due to direct limitations on animal movements and food supply chain and indirect effects due to restrictions of movements in the population, social distancing among farm and industry workers, decreases in purchasing power of the consumers and the intensification of health care task over other activities. Such impact is highly relevant because of its economical consequences, but also because of their effects on animal care and welfare due to lockdown and sanitary rules. The current review aims to offer a comprehensive overview of the impact of COVID-19 on the welfare of farm animals and livestock farming systems, on food chain sustainability and, finally, on the global economy and food security for finally offering a prospective outline of alleviation measures.